LESSON LEARNED OF USING THE VETIVER GRASS TO SOLVE HARD AND COMPACT SOIL FOR AGRICULTURE: CASE STUDY OF VILLAGES AROUND THE HUAYSAICENTER, CHA-AM DISTRICT, PHETCHABURI - Wichian, Wisaruta; Leknoi, Unruan (Journal of MCU Nakhondhat, 2022)
The objectives of this research article were to Conduct lesson learned and Suggest guidelines the Campaign to promote the Utilization of Vetiver Grass to solve Hard and Compact Soil for Agriculture: Case study of Villages around the HuaySai Center, Cha-am District, Phetchaburi Province. For the Research Tools, used the Qualitative Research by In-depth Interviews the 3 groups of Key Informants, i.e., 1) Staff from HuaySai Center and Land Development Department branch Phetchaburi 2) The Network of Vetiver Grass Conservation and 3) The agriculturist who was encouraged to use the Vetiver Grass. For the operation, surveyed the agriculture area and study how about this area used the Vetiver Grass. Then, analyzed the achievement of this area according to the Theory of Change in form Expost facto research in 3 issues, i.e., Leadership Roles and Operational Strategies of Related agencies, Enabling and Obstacles factors to use the Vetiver Grass and Short-term achievement that led to Success of this area. The findings revealed that this achievements area had Leadership Roles of Related agencies to provide the knowledge about the Utilization of the Vetiver Grass and the proper Agriculture methods for the Agriculturist to realize that the Vetiver Grass can created the Sustainable Agriculture. In addition, Related agencies implemented the good strategies with the network cooperation, i.e., Participated in bundling for training, supported many resources and continuous monitored. As a result, the Agriculturist was accepted this way and can be the Model of Agriculturist. Finally, Hard and Compact Soil have been restored, this area has long-term success and tendency to Sustainable Agriculture. However, discovered the key factors of success found in the using the Vetiver Grass to solve Hard and Compact Soil for Agriculture included 1) Leadership Roles and Good Strategies of Related agencies and 2) Acceptance of the Utilization of Vetiver Grass among Agriculturist.